Carbon Sequestration Potential under Agroforestry in Rupnagar District of Punjab - Gera, Mohit; Mohan, Giresh; Bisht, N. S.; Gera, Neelu (Indian Forester, 2006)
The paper reports study on carbon sequestration potential and cost effectiveness of tree growing operations on farm lands of Rupnagar District of Punjab. Project based-comprehensive mitigation analysis process (PRO-COMAP) was used to estimate the sequestration potential between 2005 and 2030. The results show that there is a potential to sequester 821,961 tons of carbon during the period of analyses on farm lands of Rupnagar. The whole of this potential could be achieved at a negative cost where non-carbon revenue is sufficient to offset the direct costs. Agroforestry options seems to be attractive for the district as large number of farmers and land area is dedicated to agriculture, supported by availability of irrigation facilities and high productivity of land. The development of agroforestry, however, faces certain barriers due to unorganized markets, poor technical and financial support and lack of extension activities by the Government, which must be addressed before the mitigation activity is undertaken.